A method to evaluate the determinants factors of the level of service offered at airport passenger terminals: operational arrival components - Giovanna Miceli Ronzani Borille (2012)
Studies on level of service are to be found in the relevant literature spanning the last three decades, however, the majority of these focuses on airports in the USA and Europe. The first studies carried out in relation to Brazilian airports were performed in the 1980';s when level of service recommendations were related to the sizing of passenger terminal elements. The carrying out of some applied research which included Brazilian airports is to be noted, but what stands out is the lack of analyses in areas relating to passenger disembarkation. Given that this issue is not commonly dealt with in national and international literature, the purpose of this thesis is to investigate which factors influence the level of service relating to arrival components. This study also analyzes the impacts of increased demand, infrastructure characteristics and airport operational characteristics on the variables of waiting time and available area in the baggage claim areas. In addition to this, the analysis of quality and service conditions at five Brazilian airports is also justified on the basis of the saturation capacity at major airports in Brazil, the limited possibilities of developing new airports in major cities and the holding of the World Cup in Brazil in 2014 and the Olympic Games in 2016. The methodology used in this thesis combines: (i) user monitoring techniques, (ii) infrastructure analysis, (iii) simulation models and (iv) methods of Design of Experiments (DOE) using Orthogonal Arrays and Linear Regression. In this thesis 496 passengers were observed in detail at the arrival components and a simulation model was developed to analyze operations and generate level of service indicators under various alternative scenarios. The validation of the model was conducted in comparison with real system results. 720 scenarios for domestic baggage claim facilities were analyzed and different combinations of conveyor dimensions, waiting time at the baggage claim area, the proportion of passengers with two bags, and the number of passport control desks were tested. The results indicate that the level of service offered could be significantly improved by managerial decisions mainly related to the time the baggage takes to get from the aircraft to the carousel and the time passengers take to get from the aircraft to the carousel. The aim of this thesis is to make a contribution to the academic community, as well as to airport managers and the regulatory agency. By improving the standards of level of service offered by an airport, other goals can be achieved, for example, those related to improving the performance and quality of services, increasing competitive advantage, attracting new businesses and increasing airport customer satisfaction.